Length of Stay in ED for Patients Awaiting Inpatient Psychiatric Beds - Anusha Prabhu; Chun Chiang Sin Fai Lam (BJPsych Open)
Aims: The King’s Fund have noted that the number of people waiting more than 12 hours after decision to admit to admission has increased significantly over the last ten years. With increasing demand for psychiatric inpatient beds, waiting times for mental health patient admissions are projected to similarly increase. This study aimed to investigate the length of stay for patients within a large inner city emergency department (ED) awaiting a mental health inpatient admission.